CORPORATE TAX FAIRNESS IN THE DIGITAL ECONOMY: AN EVALUATION OF OECD PILLAR TWO IMPLEMENTATION - Detti Meilandri; Khalil Zaman; Rafiullah Amin (Journal Markcount Finance, 2026)
Rapid digitalization has transformed global business operations and intensified challenges associated with corporate taxation. Multinational enterprises increasingly generate substantial profits across jurisdictions without maintaining significant physical presence, creating opportunities for profit shifting, tax avoidance, and disparities in effective tax rates. OECD Pillar Two was introduced as part of the OECD/G20 Inclusive Framework to establish a global minimum corporate tax and reduce harmful tax competition. This study aims to evaluate the effectiveness of OECD Pillar Two implementation in promoting corporate tax fairness within the digital economy. A qualitative policy evaluation approach was employed through systematic analysis of international tax policy documents, OECD reports, governmental publications, and peer-reviewed academic literature published between 2021 and 2025. Findings indicate that Pillar Two has significant potential to reduce incentives for profit shifting, strengthen alignment between economic activity and tax liabilities, and enhance international tax cooperation. Evidence further suggests that successful implementation depends heavily on administrative capacity, regulatory coordination, and institutional readiness across jurisdictions. The study concludes that OECD Pillar Two represents a substantial advancement in global tax governance and corporate tax fairness; however, long-term effectiveness requires consistent implementation, strong enforcement mechanisms, and sustained international collaboration.